Fewer Anterior Cruciate Ligament Reconstruction Failures with Autografts versus Allografts - Nichols, Emma Hitt (MD Conference Express, 2014)
Anterior cruciate ligament (ACL) reconstruction with hamstring autograft resulted in fewer reconstruction failures compared with tibialis posterior tendon allograft at 10 years. This article presents data from a study that compared the long-term outcomes of autograft versus allograft ACL reconstruction.